SAT0565 Correlation of Individual HAQ Questions with Disease Activity Measures in Psoriatic Arthritis: Implications for Instrument Reduction. (9th June 2015) - Choquette, D.; Thorne, C.; Khraishi, M.; Fortin, I.; Arendse, R.; Chow, A.; Kelsall, J.; Baker, M.; Vaillancourt, J.; Sampalis, J.S.; Nantel, F.; Otawa, S.; et al.
Abstract : Background: The Health Assessment Questionnaire (HAQ) is commonly used for assessing patient-reported functional status and disease activity in psoriatic arthritis (PsA). However, it has been critiqued for being time-consuming, not easily scored and thus, not contributing to decisions in routine care (1) Objectives: The aim of this analysis was to describe the correlation of individual HAQ questions with patient and physician reported measures used in PsA and to examine whether the instrument could be reduced to better reflect routine clinical practice. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with infliximab or golimumab. Data from PsA patients treated with infliximab or golimumab in 2006-2013 were used. The correlation of each HAQ question with patient and physician (pain, patient global assessment (PtGA), SJC28, TJC28 and physician global assessment (MDGA)) reported measures were described with the Pearson's correlation coefficient. The impact of each HAQ question on the need for help in each HAQ domain was assessed with logistic regression. Factor analysis was used to assess the variability due to each question in HAQ. Results: A total of 183 PsA patients with 596 HAQ assessments were included. Individual HAQ questions correlated at different extents with each PsA measures. All questions showed higher correlations with PtGA and pain compared to MDGA. Regarding patient reported outcomes, Question 5A ("Wash/dry your entire body") showed the highest correlation, specifically with pain. The majority of HAQ questions were significantly associated with the need for help within their corresponding ability category, with the exception of questions Q3B, Q3C, Q4B, Q5C and Q8B. The results of factor analysis showed that 2 (Q1A and Q3B) out of the 20 HAQ questions accounted for 61.5% of its matrix variance, suggesting that the question on the ability to "dress, tie shoelaces and do buttons", as well as the question on the ability to "lift a full cup or glass" may be the main drivers of HAQ in PsA. Conclusions: Variability exists in the correlation of individual HAQ questions with patient and physician reported PsA measures. Pain and PtGA are significantly associated with the various domains of HAQ, while clinical outcomes (SJC28 and TJC28) and MDGA are less important. Among PsA patients, the HAQ is driven by components related to dressing and grooming and to eating abilities, suggesting that PsA patients may be facing different challenges than RA patients. This may have implications from an occupational health perspective and in the design of a shorter self-report instrument more suitable for PsA patients. References: Khanna D, et al. Arthritis Care Res. 2011;63:S486-S490. Disclosure of Interest: D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, C. Thorne: None declared, M. Khraishi: None declared, I. Fortin: None declared, R. Arendse: None declared, A. Chow: None declared, J. Kelsall Consultant for: Janssen, M. Baker: None declared, J. Vaillancourt Employee of: JSS Medical Research, J. Sampalis Shareholder of: JSS Medical Research, F. Nantel Employee of: Janssen, S. Otawa Employee of: Janssen, A. Lehman Employee of: Janssen, C. Tkaczyk Employee of: Janssen, M. Shawi Employee of: Janssen